Trans-Hudson Orogen of North America and Himalaya-Karakoram-Tibetan Orogen of Asia: Structural and thermal characteristics of the lower and upper plates - St-Onge, MR; Searle, M; Wodicka, N (2006)
The Trans-Hudson Orogen (THO) of North America and the Himalaya-Karakoram- Tibetan Orogen (HKTO) of Asia preserve a Paleoproterozoic and Cenozoic record, respectively, of continent-continent collision that is notably similar in scale, duration and character. In THO, the tectonothermal evolution of the lower plate involves (1) early thin-skinned thrusting and Harrovian metamorphism, (2) out-of-sequence thrusting and high-T metamorphism, and (3) fluid-localized reequilibration, anatexis, and leucogranite formation. The crustal evolution of the Indian lower plate in HKTO involves (1) early subduction of continental crust to ultrahigh pressure (UHP) eclogite depths, (2) regional Barrovian metamorphism, and (3) widespread high-T metamorphism, anatexis, and leucogranite formation. The shallow depths of the high-T metamorphism in HKTO are consistent with early to mid-Miocene ductile flow of an Indian lower plate midcrustal channel, from beneath the southern Tibetan Plateau to the Greater Himalaya. Melt weakening of the lower plate in THO is not observed at a similar scale probably due to the paucity of pelitic lithologies. Tectonothermal events in the upper plate of both orogens include precollisional accretion of crustal blocks, emplacement of Andean-type plutonic suites, and high-T metamorphism. Syncollisional to postcollisional events include emplacement of garnet-biotite-muscovite leucogranites, anatectic granites, and sporadic metamorphism (up to 90 Myr following the onset of collision in THO). Comparing the type and duration of tectonothermal events for THO and HKTO supports the notion of tectonic uniformitarianism for at least the later half of dated Earth history and highlights the complementary nature of the rock record in an older "exhumed" orogen compared to one undergoing present-day orogenesis. Copyright 2006 by the American Geophysical Union.